Legal Protection for E-commerce Business Actors regarding Consumer Reviews - Julia Choeirunnissa; Martin Situmorang; Muhamad Zidan; Endang Sutrisno; Alip Rahman (Riviera Publishing, 2024)
Customer reviews in e-commerce play an important role in influencing the decisions made by customers. Before making a purchase, many people read positive customer reviews because they can offer useful information to potential buyers and increase their overall level of trust in the product. The purpose of this research is to analyse the good faith of business actors and how it impacts the law stipulated in the Consumer Protection Law. This research utilizes a normative legal research study whose findings show that consumers are not liable for criticism that harms businesses, according to the Consumer Protection Law (UUPK). In particular, Article 5a requires consumers to pay special attention to product descriptions listed in stores. In the e-commerce business world, business actors utilize the latest technology such as the internet to facilitate their business activities, yes; they get a number of benefits such as serving customers and making it easier to access distant information more quickly. If business actors receive negative reviews from consumers that do not match the facts so as to cause losses to business actors, the legal protection for business actors based on a positive legal perspective will be analysed. Based on the results of the analysis, it is found that giving negative reviews by consumers without a clear explanation and not according to the facts can harm business actors. This is considered a bad faith action by consumers.